Using invasive weed (Bidens pilosa L.) as a feed supplement to promote Nile tilapia (Oreochromis niloticus) health - Nantaporn Sutthi; Eakapol Wangkahart; Wipavee Thaimuangphol; Prasoborn Rinthong; Laorsri Sanoamuang (Aquaculture Reports)
Bidens pilosa is a widespread invasive species typically regarded as a weed with no economic value. Repurposing this plant as a functional feed ingredient presents a sustainable, cost-effective approach for aquaculture. This study evaluated the effects of adding dietary B. pilosa leaf ethanol extract on growth performance, immune responses, gene expression, and disease resistance in Nile tilapia. Experimental diets supplemented a basal feed with B. pilosa extract at 2.5 g/kg (T2), 5.0 g/kg (T3), and 10.0 g/kg (T4); the control group (T1) received no supplementation. After a 60-day feeding trial, fish in the T2 exhibited significantly higher weight gain, daily growth rate, and an improved feed conversion ratio (FCR) compared with the control group (P < 0.05). Additionally, the T2 group had the highest fillet yield and the lowest carcass yield (P < 0.05). Biochemical analyses revealed that the highest extract level (T4) induced oxidative stress and immune dysregulation, including both immune suppression and potential ineffective immunity, evidenced by elevated aspartate aminotransferase (AST) and malondialdehyde (MDA) levels, alongside decreased lysozyme activity (LZM), myeloperoxidase (MPO), red blood cell (RBC) count, and hemoglobin (Hb) concentration (P < 0.05). In contrast, the T2 group exhibited the highest post-challenge survival (53.33 ± 15.27 %) against Streptococcus agalactiae and upregulated growth hormone (GH) and glutathione peroxidase (GPx) gene expression (P < 0.05). Quadratic regression analysis estimated the optimal inclusion level at 4.29–4.58 g/kg. These findings demonstrate that supplementation at 2.5 g/kg enhances growth, immune competence, and disease resistance in Nile tilapia, whereas excessive inclusion (10 g/kg) may provoke oxidative stress, dual immune suppression, and inflammatory toxicity, underscoring the importance of precise dosage optimization for sustainable aquaculture.